Regulation of epithelial plasticity determines metastatic organotropism in pancreatic cancer - Reichert, Maximilian; Kriegsmann, Mark (Developmental cell, 2018)
The regulation of metastatic organotropism in pancreatic ductal a denocarcinoma (PDAC) remains poorly understood. We demonstrate, using multiple mouse models, that liver and lung metastatic organotropism is dependent upon p120catenin (p120ctn)-mediated epithelial identity. Mono-allelic p120ctn loss accelerates KrasG12D-driven pancreatic cancer formation and liver metastasis. Importantly, one p120ctn allele is sufficient for E-CADHERIN-mediated cell adhesion. By contrast, cells with bi-allelic p120ctn loss demonstrate marked lung organotropism; however, rescue with p120ctn isoform 1A restores liver metastasis. In a p120ctn-independent PDAC model, mosaic loss of E-CADHERIN expression reveals selective pressure for E-CADHERIN-positive liver metastasis and E-CADHERIN-negative lung metastasis. Furthermore, human PDAC and liver metastases support the premise that liver metastases exhibit predominantly epithelial characteristics. RNA-seq demonstrates differential induction of pathways associated with metastasis and epithelial-to-mesenchymal transition in p120ctn-deficient versus p120ctn-wild-type cells. Taken together, P120CTN and E-CADHERIN mediated epithelial plasticity is an addition to the conceptual framework underlying metastatic organotropism in pancreatic cancer.